TEMPORAL TRENDS OF CLIMATE INDICES ASSOCIATED WITH PRECIPITATION AND AIR TEMPERATURE IN MINAS GERAIS, BRAZIL - Oliveira, Alisson Souza de; Mello, Carlos Rogério de; Marques, Rodângela Francisca de Paula Vitor (Revista Brasileira de Climatologia, 2021)
The objective of this study was to evaluate the trends of four climatic extremes indices related to minimum and maximum air temperatures and three related to precipitation in Minas Gerais state, Brazil, from 1961 to 2010. These indices were developed by the Expert Team on Climate Change Detection Monitoring and Indices (ETCCDMI) with the aim of subsidizing climate change on global, regional and local levels. Daily rainfall and temperature long-term series were obtained from the National Institute of Meteorology (INMET) for 47 municipalities, in different regions of the state. The analyzes were conducted considering the four seasons of the year based on the Mann-Kendall and linear regression tests. There was a significant trend towards change in the indices related to minimum (TNn; TNx) and maximum (TXn; TXx) temperatures all over the state. Precipitation indexes (R10mm, R20mm and SDII) have showed no significant changes. The increase in the TNn, TNx, TXn and TXx has been observed in all seasons, except for autumn, and the TNx index in the winter. Both minimum and maximum temperatures indices have showed increase in greatest part of Minas Gerais in the spring, evidencing an expressive heating in this season and a premature summer onset. In the autumn, there was a downward trend in all temperature indices, characterizing an anticipation of winter. In winter, there was an upward trend in the TNn index and downward of the TNx in almost the entire state, indicating a reduction in the frost occurrence possibility, especially in the South and Southeast regions. The highest rates were observed in the Mid-west and Northwest regions. For the TXx index, in the summer there were upward trends throughout the state, especially in the North. Thus, important consequences to the agriculture planning and zoning have taken place as well as a proliferation of arbovirus diseases, affecting the life quality of the population.